Classic Essays on Twentieth-Century Music: A Continuing Symposium - Kostelanetz, Richard; Darby, Joseph; Santa, Matthew; Ives, Charles 1874-1954; Gershwin, George 1898-1937; Varèse, Edgard 1883-1965; Schoenberg, Arnold 1874-1951; Joyce, James 1882-1941 (New York Schirmer, 1996)
Thirty-five essays explore major topics in modern music, including Machine Art, Electronic Art and the Aesthetics of Technology; Perspectives on Composers and Modern Society; Sound Space, and Meaning; Twelve-Tone and Serial Composition; Music Among the Arts; and Jazz and Popular Music. Includes contributions from Ives, Gershwin, Varése, Schoenberg, Babbitt, James Joyce, Amiri Baraka, and more.
Keywords: 20th Century (1901-2000); Composer